Taken lives matter: open justice and recognition in inquests into deaths at the hands of the state. Issue 2 (22nd June 2016) - McIntosh, Sam
Abstract: Lord Neuberger describes open justice as a procedural principle requiring that 'what goes on in court and what a court decides is open to scrutiny' (Neuberger, 2011). The prime rationale given for this principle is that it is a safety check on procedural fairness. Such a conception of open justice applies on only a superficial level in inquests into use-of-force deaths at the hands of the state. This paper examines the practice of, and rationales behind, opening up use-of-force deaths at the hands of the state to scrutiny through inquests. They suggest a primarily intrinsic rather than instrumental link between openness and inquests' purposes, which requires a reframing of traditional conceptions of open justice in this context. It is further argued that recognition theory can provide the normative link between openness and justice in these circumstances – a link that is implicit in the term 'open justice' but rarely explored in inquests.